PENDIDIKAN AGAMA ISLAM BERBASIS NASIONALISME - Mursidin Mursidin (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2019)
AbstractThis article explains about Islamic education based on Nationalism. Islamic education is not only taught in formal teachings in schools, but also in non-formal education. This fact must be recognized and received attention, because if not then Islamic education is felt to be lame. Therefore, when talking about Islamic education, what is considered is the whole aspects which are also included in it reviewing nationalism. Therefore, it can be concluded that the depletion of national ties due to religion did occur, this is indicated by the emergence of separatist movements in Indonesia. However, this is not because of religious teachings (especially Islam) which do not support nationalism, but because of the followers of the religion experience silence in understanding religious texts. This is where the importance of Islamic education is. That is as a media for inclusive and contextual Islamic understanding. Because until now education is believed to be the most powerful means for the process of transforming values, including the values of nationalism in Islam. Keywords: Islamic Education; Nationalism. AbstrakArtikel ini memaparkan tentang pendidikan agama Islam berbasis Nasionalisme. Pendidikan Islam tidak hanya diajarkan dalam ajaran-ajaran formal di sekolah semata, melainkan pendidikan non formal. Kenyataan ini harus diakui dan mendapat perhatian, karena jika tidak maka pendidikan Islam dirasa pincang. Karena itu, ketika berbicara mengenai pendidikan Agama Islam, maka yang dipikirkan adalah keseluruhan aspek yang juga tercakup di dalamnya megnkaji tentang nasionalisme. Oleh karena itu dapat disimpulkan bahwa menipisnya ikatan kebangsaan karena agama memang terjadi, hal ini dindikasikan oleh munculnya gerakan-gerakan separatis di Indonesia. Akan tetapi hal itu bukan karena ajaran agama (khususnya Islam) yang tidak mendukung nasionalisme akan tetapi karena para pemeluk agama mengalami pendangkalan pemahaman teks-teks keagamaan. Disinilah arti penting pendidikan Islam. Yaitu sebagai media transfer pemahaman keIslaman yang inklusif dan kontekstual. Karena sampai sekarang pendidikan dipercaya sebagai sarana paling ampuh untuk proses transformasi nilai, termasuk nilai-nilai nasionalisme dalam Agama Islam. Kata Kunci: Pendidikan Agama Islam; Nasionalisme.